High Performance and Structural Stability of K and Cl Co-Doped LiNi0.5Co0.2Mn0.3O2 Cathode Materials in 4.6 Voltage - Chen, Zhaoyong; Gong, Xiaolong; Zhu, Huali; Cao, Kaifeng; Liu, Qiming; Liu, Jun; Li, Lingjun; Duan, Junfei (Frontiers in Chemistry, 2019)
ABSTRACT The high energy density lithium ion batteries are being pursued because of their extensive application in electric vehicles with a large mileage and storage energy station with a long life. So, increasing the charge voltage becomes a strategy to improve the energy density. But it brings some harmful to the structural stability. In order to find the equilibrium between capacity and structure stability, the K and Cl co-doped LiNi0.5Co0.2Mn0.3O2 (NCM) cathode materials are designed based on defect theory, and prepared by solid state reaction. The structure is investigated by means of X-ray diffraction (XRD), rietveld refinements, scanning electron microscope (SEM), XPS, EDS mapping and transmission electron microscope (TEM). Electrochemical properties are measured through electrochemical impedance spectroscopy (EIS), cyclic voltammogram curves (CV), charge/discharge tests. The results of XRD, EDS mapping and XPS show that K and Cl are successfully incorporated into the lattice of NCM cathode materials. Rietveld refinements along with TEM analysis manifest K and Cl co-doping can effectively reduce cation mixing and make the layered structure more complete. After 100 cycles at 1 C, the K and Cl co-doped NCM retains a more integrated layered structure compared to the pristine NCM. It indicates the co-doping can effectively strengthen the layer structure and suppress the phase transition to some degree during repeated charge and discharge process. Through CV curves, it can be found that K and Cl co-doping can weaken the electrode polarization and improve the electrochemical performance. Electrochemical tests show that the discharge capacity of Li0.99K0.01(Ni0.5Co0.3Mn0.2)O1.99Cl0.01 (KCl-NCM) are far higher than NCM at 5 C, and capacity retention reaches 78.1% after 100 cycles at 1 C. EIS measurement indicates that doping K and Cl contributes to the better lithium ion diffusion and the lower charge transfer resistance. Key words: lithium ion batteries; LiNi0.5Co0.2Mn0.3O2; co-doping; cation mixing; phase transition.